ANALISIS BIAYA PENGOBATAN PASIEN DIABETES MELLITUS RAWAT JALAN DI RSUD KRATON PEKALONGAN - Wulan Agustin Ningrum; Ainun Muthoharoh; Mar’atul Qoyimah (LPPM Universitas Pekalongan, 2019)
Diabetes mellitus is a chronic disease that requires long treatment therapy and requires a large cost. This research aims to determine the most cost effective oral antidiabetic treatment of diabetes mellitus type 2 in outpatients in RSUD Kraton Pekalongan. This research type is non experimental research with descriptive method. Data retrieval was conducted in a retrospective study. Processing on the research done by using t-test. The results of the most cost-effectiveness treatment pattern is sulphonylurea and biguanid treatment pattern with an average total cost of Rp. 237.499,44. Value of ACER (Average Cost-Effectiveness Ratio) can be seen from the effectiveness based on blood glucose level reaching target which is equal to 55,56% which is lower if compared with other treatment pattern that is Rp. 427.499,00.